UNIT 6.17 Methods to Detect Protein Glutathionylation. Issue 1 (23rd September 2013) - Poerschke, Robyn L.; Fritz, Kristofer S.; Franklin, Christopher C.
Abstract: Glutathionylation is a posttranslational modification that results in the formation of a mixed disulfide between glutathione and the thiol group of a protein cysteine residue. Glutathionylation of proteins occurs via both nonenzymatic mechanisms involving thiol/disulfide exchange and enzyme‐mediated reactions. Protein glutathionylation is observed in response to oxidative or nitrosative stress and is redox‐dependent, being readily reversible under reducing conditions. Such findings suggest that glutathionylation plays an important role in mediating redox‐sensitive signaling. Indeed, glutathionylation can affect protein function by altering activity, protein‐protein interactions, and ligand binding. Glutathionylation may also serve to prevent cysteine residues from undergoing irreversible oxidative modification. Thus, determining the ability of a given protein to become glutathionylated can provide insight into its redox regulation and putative role in dictating cellular response to oxidative and nitrosative stress. Methods to measure protein glutathionylation using immunoblotting and mass spectrometry are described. Curr. Protoc. Toxicol . 57:6.17.1‐6.17.18. © 2013 by John Wiley & Sons, Inc.